Desain dan Implementasi Kurikulum Muadalah di Pondok Pesantren Darussalam Ciomas Bogor - Fachru Abdul Rahman (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This muadalah curriculum is an independent curriculum according to the boarding school that developed it, curriculum independence includes aspects in determining teaching materials, assessment systems, and learning processes. This study uses a qualitative approach. The data collection was carried out by sourced from several documents of the muadalah curriculum contained in the boarding school, as well as interviews with parties related to the muadalah curriculum, and observations of researchers with field reviews of the process of implementing the learning of the muadalah curriculum at Islamic boarding schools. Darussalam. The results of the research show that the type of curriculum design is the Darussalam Islamic Boarding School, including the type of separated subject curriculum design. The subject curriculum consists of separate subjects, and